Plate-like alumina powder, its manufacturing method, and paint or cosmetic

By controlling the particle size, thickness and polycrystalline structure of the plate-shaped aluminum oxidized powder, the problem of scattered light effect in the prior art is solved, and the effect of high brightness and low scattered light is achieved, which is suitable for beauty products and other applications.

JP7663150B1Active Publication Date: 2025-04-16NIPPON LIGHT METAL CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024185920
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-04-16
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

When existing plate-shaped aluminum oxidized powders increase the particle size to utilize their high reflectivity, they are prone to glare effects, especially in beauty products.

Method used

By controlling the average particle size and thickness of the plate-shaped aluminum oxidized powder and making it a polycrystalline structure, the average particle size is between 2 microns and 100 microns and the average thickness is between 0.2 microns and 3.0 microns, while controlling the ratio of the particle boundary length to the particle boundary perimeter to reduce the scattered light effect.

Benefits of technology

It realizes that the glare effect is reduced while maintaining the same particle size, thereby improving the brightness and aesthetics of the powder, and is suitable for applications such as beauty products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663150000001_ABST
    Figure 0007663150000001_ABST
Patent Text Reader

Abstract

To provide a plate-like alumina powder which has less dotted shine (glare) compared with conventional plate-like alumina powders even though the particle size is the same, and a method for producing the same. [Solution] The plate-like alumina powder is composed of a plurality of plate-like alpha-alumina particles, has an average particle diameter of 2 μm or more and 100 μm or less, and an average thickness of 0.2 μm or more and 3.0 μm or less, wherein the plate-like alpha-alumina particles are polycrystalline, and on the plate surfaces of the plate-like alpha-alumina particles, the average ratio (L2 / L1) of the total length of the grain boundaries (L2) to the circumferential length (L1) of the plate-like alpha-alumina particles is 0.30 or more and 2.00 or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a platelet alumina powder, a method for producing the same, and a paint or cosmetic. [Background technology]

[0002] Alumina (Al2O3) is chemically stable and has excellent heat resistance, corrosion resistance, wear resistance, and insulation properties, as well as high strength and hardness. Taking advantage of these characteristics, alumina powder is widely used in a variety of applications, including structural members, tools, abrasives, fillers, spark plugs, insulators, electronic substrates, and refractories.

[0003] In particular, plate-like alumina powder has a high light reflectance and high brightness on its particle surface. Therefore, by taking advantage of this characteristic, it is used as a pigment added to paints and cosmetics. Note that plate-like alumina powder is a powder composed of multiple plate-like alumina particles, and is also called scaly alumina powder, flaky alumina powder, flat alumina powder, or alumina flakes.

[0004] As a document disclosing the use of platelet alumina powder as a pigment, Patent Document 1 discloses a platelet alumina powder having a thickness of 500 nm or more and a D of 15 to 30 μm. 50 value and D of 30 to 45 μm 90 It is disclosed that Al2O3 flakes having a value of 0.1 to 1.0, which simultaneously have high chemical stability, a smooth surface, and high whiteness, are used as a pigment substrate (claim 1,

[0010] and

[0015] of Patent Document 1). Patent Document 1 also describes that the Al2O3 flakes are coated with a high refractive index layer such as TiO2 or a low refractive index layer such as SiO2, which gives them increased luster, interference color, or color flop effect (

[0040] to

[0046] of Patent Document 1).

[0005] Patent Document 2 discloses a paint composition containing alumina flakes as a luster pigment, and describes that it can be suitably used as an automobile top coat, and that it forms a composite coating film with unprecedented high luster and novel designability without compromising the finished appearance (claim 1,

[0001] and

[0108] of Patent Document 2). Patent Document 2 also describes that the alumina flakes are aluminum oxide (Al2O3) coated with a metal oxide such as titanium dioxide, with a particle size of 10 to 30 μm and a thickness of 0.3 to 0.4 μm (

[0007] of Patent Document 2).

[0006] Patent Document 3 discloses a pearlescent pigment containing aluminum oxide and zinc oxide as main components in a mass ratio of 100:0.1-5, and containing flaky alumina crystals coated with metal or metal precursor particles (claim 1 of Patent Document 3). Patent Document 3 also describes that the crystals have an average particle thickness of 0.5 μm or less, an average particle size of 15 μm or more, and an aspect ratio of 50 or more, and therefore have excellent gloss (

[0001] of Patent Document 3).

[0007] Patent Document 4 discloses a method for producing a plate-like alumina-based powder characterized by having a crystal structure of only α-, β-, or γ-alumina, or two or more types of crystal structures, by firing plate-like boehmite at 400° C. to 1500° C. (Claim 2 of Patent Document 4). Patent Document 4 also discloses that a cosmetic product with a good feel can be obtained by surface-coating plate-like boehmite or plate-like alumina powder with a hydrophobic compound such as polysiloxane and incorporating the coated powder into a cosmetic product (

[0013] of Patent Document 4).

[0008] Patent Document 5 discloses hexagonal plate-like alumina obtained by firing hexagonal plate-like boehmite at temperatures of 450 to 1500°C. The hexagonal plate-like alumina has a roughly hexagonal plate shape, a ratio of the major axis to the minor axis of 1 to 1.3, and an aspect ratio of 40 to 100. The document describes that the hexagonal plate-like alumina has high orientation, reduces diffuse reflection, and enhances brilliance, and can also be suitably used as a filler for the purpose of increasing the brilliance of paints and cosmetics (Claim 4 and

[0045] of Patent Document 5).

[0009] Patent Document 6 discloses plate-like alumina particles having a thickness of 0.01 to 5 μm, an average particle diameter of 0.1 to 500 μm, an aspect ratio (the ratio of the particle diameter to the thickness) of 2 to 500, a polygonal plate shape, and containing molybdenum within the particles (Claim 1 of Patent Document 6). Patent Document 6 also discloses that the plate-like alumina particles can be suitably used for thermally conductive fillers, cosmetics, abrasives, high luster pigments, lubricants, substrates for conductive powders, ceramic materials, and the like (

[0101] of Patent Document 6). [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2014-218424 A [Patent Document 2] Japanese Patent Application Publication No. 10-298458 [Patent Document 3] Special Publication No. 2010-502774 [Patent Document 4] JP 2012-071996 A [Patent Document 5] JP 2003-002642 A [Patent Document 6] JP 2019-123664 A Summary of the Invention [Problem to be solved by the invention]

[0011] Thus, although research has been conducted to improve the brilliance of plate-like alumina powder, there is still room for improvement in conventional plate-like alumina powders. In other words, in order to take advantage of the high reflectance of plate-like alumina powder, it is effective to increase the particle size of the powder.

[0012] However, if the particle size becomes too large, the scattered shine (glare) becomes stronger. Here, scattered shine refers to a state in which areas of high brightness (bright spots) exist locally in the powder. For example, when the brightness from the particles constituting the plate-like alumina powder varies greatly depending on the particle orientation (angle between the particle and the observation direction), the brightness from a specific part becomes strong. Such scattered shine (glare) may be undesirable depending on the application. In particular, pigments with scattered shine tend to be avoided in cosmetic applications.

[0013] The present inventors have conducted extensive research in light of these problems, and as a result have discovered that a plate-like alumina powder having a specific average particle size and average thickness as well as a specific polycrystalline state has less dotted sparkle (glare) than a conventional plate-like alumina powder, even if the particle size is the same.

[0014] The present invention was completed based on such findings, and an objective of the present invention is to provide a plate-like alumina powder that has reduced dotted shine (glare) compared to conventional plate-like alumina powders, even though the particle size is the same, and a method for producing the same. [Means for solving the problem]

[0015] The present invention encompasses the following aspects (1) to (8). In this specification, the expression "to" includes both ends of the expression. In other words, "X to Y" is synonymous with "X or more and Y or less."

[0016] (1) A plate-like alumina powder composed of a plurality of plate-like α-alumina particles, having an average particle size of 2 μm or more and 100 μm or less and an average thickness of 0.2 μm or more and 3.0 μm or less, The plate-like α-alumina particles are polycrystalline, The plate-like alumina powder has an average ratio (L2 / L1) of the total length (L2) of the grain boundaries to the circumferential length (L1) of the plate-like alpha-alumina particles on the plate surfaces of the plate-like alpha-alumina particles of 0.30 or more and 2.00 or less.

[0017] (2) The platelet alumina powder according to (1) above, wherein the average value of L2 / L1 is 0.50 or more and 1.50 or less.

[0018] (3) The plate-like alumina powder according to (1) or (2) above, wherein the average particle size is 5 μm or more and 50 μm or less, and the average thickness is 0.3 μm or more and 1.0 μm or less.

[0019] (4) A method for producing a plate-like alumina powder according to any one of (1) to (3), comprising the steps of: Preparing a raw material mixture containing aluminum hydroxide powder and an additive; and A step of firing the raw material mixture at a temperature in the range of 1000° C. to 1300° C. for less than 20 hours, The raw material mixture contains an alkali metal (AM) in an amount of 0.01% by mass or more and 0.5% by mass or less in terms of AM2O, silicon (Si) in an amount of 0.1% by mass or more and 0.3% by mass or less in terms of SiO2, and fluorine (F) in an amount of 0.1% by mass or more and 5.0% by mass or less in terms of F, The method, wherein the heating rate in the step of firing the raw material mixture is 50° C. / hour or more and 150° C. / hour or less.

[0020] (5) The method according to (4) above, wherein the additive comprises an alkali silicofluoride (AM2SiF6), or aluminum fluoride (AlF3) and silicon oxide (SiO2).

[0021] (6) The method according to (5) above, wherein the additive further comprises one or both of an oxide (AM2O) and a carbonate (AM2CO3) of an alkali metal (AM).

[0022] (7) The method according to any one of (4) to (6) above, wherein the alkali metal (AM) is one or both of sodium (Na) and potassium (K).

[0023] (8) A paint or cosmetic comprising the platelet alumina powder according to any one of (1) to (3) above. Effect of the Invention

[0024] According to the present invention, there are provided a plate-like alumina powder which has less scattered shine (glare) compared to conventional plate-like alumina powders even though the particle size is the same, and a method for producing the same. [Brief description of the drawings]

[0025] [Figure 1] The mechanism by which platelet alumina powder creates a shiny appearance is shown below. [Diagram 2] 1 shows a schematic diagram of the scattering of light passing through a polycrystalline material. [Diagram 3] 1 shows a schematic diagram of a plate surface of a plate-like particle. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] A specific embodiment of the present invention (hereinafter referred to as "the present embodiment") will be described below. However, the present invention is not limited to the following embodiment, and various modifications are possible within the scope of the present invention. In addition, in this specification, any combination of suitable aspects can be adopted as long as technical consistency can be achieved. For example, one of the suitable numerical ranges can be combined with the other.

[0027] <<1. Plate-shaped alumina powder>> The plate-like alumina powder of this embodiment (hereinafter, sometimes simply referred to as "alumina powder") is composed of a plurality of plate-like alpha-alumina (Al2O3) particles (hereinafter, sometimes simply referred to as "alumina particles", "plate-like particles", or "particles"). That is, it contains plate-like alpha-alumina particles as a main component. Here, the plate-like alpha-alumina particles are particles made of alpha-alumina (corundum). Alpha-alumina has trigonal corundum crystals, and is excellent in chemical stability, heat resistance, corrosion resistance, wear resistance, and insulation, and has high strength and hardness. In addition, it has high light reflectance, brightness, and whiteness. Since the alumina powder of this embodiment contains plate-like alpha-alumina particles as a main component, it is possible to fully utilize these characteristics.

[0028] In this specification, powder means an aggregate of many independent particles. In other words, many particles aggregate to form a powder. Since each particle that constitutes a powder is independent, the powder exhibits overall fluidity in its own state. It is sufficient that most of the particles that constitute a powder are independent. As long as the powder exhibits overall fluidity, some particles may be bonded to form aggregates. In addition, an aggregate of many particles dispersed in a medium such as a liquid or resin is also called a powder.

[0029] In the plate-like alumina powder of this embodiment, the shape of the alumina particles constituting the plate-like alumina powder is plate-like (scale-like, thin-flaky, flat, flake-like). That is, each particle has a large plate surface and a small plate thickness. Specifically, the average particle diameter of the plate-like alumina powder is 2 μm or more and 100 μm or less, and the average thickness is 0.2 μm or more and 3.0 μm or less. Here, the average particle diameter and the average thickness are the average values ​​of the particle diameter and thickness of each particle constituting the alumina powder based on the number of particles. In addition, the particle diameter is the long diameter of the particle. In other words, the long axis diameter of the particle plate surface is the particle diameter. In addition, the thickness is the plate thickness of the plate surface. The particle diameter and thickness can be obtained by observing the particles constituting the alumina powder with a scanning electron microscope (SEM). In other words, the average particle diameter and the average thickness are values ​​obtained by SEM observation. In addition, the average particle diameter is usually larger than the average thickness.

[0030] In this way, by using particles with large plate surfaces and small plate thickness, the brilliance of the alumina powder can be increased. This point will be explained with reference to FIG. 1. As shown in FIG. 1, when a powder containing particles with large plate surfaces and small plate thickness is formed on a substrate by a method such as coating, the particle plate surfaces with large areas tend to be oriented so that they are aligned parallel to the substrate surface. The larger the particle diameter, the larger the surface area of ​​the particle plate surfaces aligned parallel to the substrate surface. Furthermore, light incident from the outside is reflected by the particle plate surfaces and radiated to the outside as reflected light. Therefore, the larger the particle diameter, the easier it is for the incident light to be reflected by the particle plate surfaces, resulting in a higher visual brilliance.

[0031] If the average particle size is less than 2 μm or the average thickness is more than 3.0 μm, the brilliance of the powder may be insufficient. On the other hand, if the average particle size is more than 100 μm or the average thickness is less than 0.2 μm, it is difficult to manufacture the powder. In addition, the strength is low and handling is difficult. The average particle size of the plate-like alumina powder is preferably 5 μm or more and 50 μm or less, and the average thickness is preferably 0.3 μm or more and 1.0 μm or less.

[0032] The average aspect ratio of the alumina powder is preferably 20 or more and 50 or less. Here, the average aspect ratio is the ratio of the average particle diameter to the average thickness (average particle diameter / average thickness). By making the average aspect ratio 20 or more, it is possible to further enhance the brilliance of the powder. Also, by making the average aspect ratio 50 or less, the strength of the alumina powder is increased and handling becomes easier.

[0033] It is not necessary that all particles constituting the alumina powder are plate-like alpha-alumina particles. As long as the alumina powder as a whole satisfies the above-mentioned requirements for the average particle size and average thickness, it may contain particles other than plate-like alpha-alumina particles. However, in order to take advantage of the excellent effects based on the plate-like alpha-alumina particles, it is preferable that the content of the plate-like alpha-alumina particles is high. The content of the plate-like alpha-alumina particles is preferably 80 mass% or more, more preferably 90 mass% or more, and even more preferably 95 mass% or more.

[0034] The alumina powder of this embodiment is made up of plate-like α-alumina particles that are polycrystalline. In other words, each particle is not made up of one single crystal, but is made up of multiple crystallites (or crystal grains). In each particle, adjacent crystallites are in contact with each other via grain boundaries. In addition, on the plate surface of the plate-like α-alumina particles, the average value of the ratio (L2 / L1) of the total length (L2) of the grain boundaries to the perimeter (L1) of the plate-like α-alumina particles is 0.30 or more and 2.00 or less. In this way, by making the alumina particles polycrystalline and limiting the ratio (L2 / L1) of the perimeter to the grain boundary length to a predetermined range, it is possible to suppress the scattered sparkle (glare).

[0035] This point will be explained using Figure 2, which shows a schematic diagram of the scattering of light passing through a polycrystalline body. When the crystal form of the alumina particles is polycrystalline, the crystal structure inside each crystallite contained in the polycrystal is aligned, and the refractive index is uniform. Therefore, the light passing through the crystallite travels straight without being scattered. On the other hand, the crystal structure is disordered at the grain boundaries, and in some cases it is amorphous. Therefore, the refractive index changes at the grain boundaries. Therefore, light does not travel straight at the grain boundaries, but is scattered in all directions. As a result, the reflected light is weakened, and the glare can be suppressed. On the other hand, when the alumina particles are single crystal, the scattered light is suppressed and the reflected light is strengthened, resulting in excessive glare.

[0036] The scattered sparkle (glittering) can be controlled by adjusting the proportion of the grain boundary portion in each particle. The proportion of the grain boundary portion can be estimated by the ratio (L2 / L1) of the total length of the grain boundaries (L2) to the perimeter of the particle (L1). Here, as shown in FIG. 3, the perimeter of the particle (L1) is the perimeter of the plate surface of the plate-like particle. The total length of the grain boundaries (L2) is the total value of the grain boundary lengths exposed on the plate surface of the plate-like particle. Note that FIG. 3 shows the plate surface of the plate-like particle as a schematic diagram. In FIG. 3, L1 is shown by a solid line, and L2 is shown by a dashed line. Furthermore, L2 / L1 is the ratio of the perimeter of each particle (L1) to the total grain boundary length (L2), and the average value of L2 / L1 is the average value of the ratios (L2 / L1) in multiple particles.

[0037] If the average value of L2 / L1 is 0.30 or more and 2.00 or less, the proportion of the grain boundary portion is appropriate, and it is possible to achieve both high brilliance and suppressed glittering. On the other hand, if the average value of L2 / L1 is less than 0.30, the proportion of the grain boundary portion is insufficient, and the effect of reducing glittering by light scattering is insufficient. On the other hand, if the average value of L2 / L1 is more than 2.00, the proportion of the grain boundary portion becomes excessively large, which increases scattered light, weakens reflected light, and causes a loss of brilliance. From the viewpoint of achieving a further balance between high brilliance and suppressed glittering, the average value of L2 / L1 is preferably 0.40 or more and 1.80 or less, and more preferably 0.50 or more and 1.50 or less.

[0038] Whether or not the plate-like alpha-alumina particles are polycrystalline can be determined by observing the particles with an SEM. The average value of L2 / L1 can also be determined by observing the plate-like alumina powder with an SEM. Specifically, when the surface or cross section of a particle is observed with an SEM, the grain boundaries of the crystals are observed, and it can be confirmed that the plate-like alpha-alumina particles are polycrystalline. The ratio of the grain boundary length on the particle surface to the outer periphery of the particle can be determined from the ratio of L1 and L2, and this can be evaluated as the degree of polycrystallinity.

[0039] In the plate-like alumina powder of the present embodiment, in a powder X-ray diffraction (XRD) pattern obtained in an oriented state, it is preferable that the intensity ratio of the diffraction peak due to α-alumina is within a predetermined range. Specifically, the intensity I of the diffraction peak due to the (006) plane of α-alumina is A and the intensity of the diffraction peak due to the (113) plane of α-alumina I B Ratio to (I A / I B ) is preferably 0.3 or more and 10 or less. The intensity I of the diffraction peak due to the (104) plane of α-alumina C and the intensity of the diffraction peak due to the (113) plane of α-alumina I B Ratio to (I C / I B ) is preferably 4.0 or more and 10 or less. In addition, the intensity ID and the intensity of the diffraction peak due to the (113) plane of α-alumina I B Ratio to (I D / I B ) is preferably 3.0 or more and 7.5 or less. The intensity I of the diffraction peak due to the (018) plane of α-alumina E and the intensity of the diffraction peak due to the (113) plane of α-alumina I B Ratio to (I E / I B ) is preferably 1.0 or more and 7.5 or less. The intensity I of the diffraction peak due to the (1010) plane of α-alumina F and the intensity of the diffraction peak due to the (113) plane of α-alumina I B Ratio to (I F / I B ) is preferably 5.0 or more and 20.0 or less.

[0040] The (006) plane of α-alumina corresponds to a crystal plane (c-plane) perpendicular to the c-axis of the α-alumina crystal. The (104), (116), (018), and (1010) planes of α-alumina are all crystal planes with small angles to the c-plane, that is, crystal planes similar to the c-plane. The plate-like alumina powder of this embodiment is composed of plate-like α-alumina particles with large plate surfaces and small plate thicknesses. Therefore, when the plate-like alumina powder is filled into a measurement holder to obtain a powder XRD pattern, the plate-like α-alumina particles are oriented so that the plate surfaces of the particles are aligned with the measurement surface. Therefore, in the XRD pattern of the plate-like alumina powder, the diffraction peak intensity (I A , I C , I D , I E and I F ) is strongly observed.

[0041] The XRD pattern in the oriented state can be obtained as follows. The sample is placed on a glass sample plate, pressed so that the sample surface is flat, and then measured with an XRD measuring device. Since the sample is a plate-shaped particle, when the powder sample is filled, it is likely to be aligned with a specific crystal axis relative to the surface of the sample plate, resulting in a preferential orientation effect. If the plate-shaped alumina powder is pulverized when preparing a measurement sample, the shape of the powder changes, which may impair the preferential orientation effect. Therefore, the measurement is performed without adjusting the particle size. In addition, in this specification, the peak intensity means the peak area (integral intensity). In addition, when CuKα is used as the X-ray source, the diffraction peak based on the (006) plane of α-alumina appears at 2θ=41.7±0.5°. Similarly, the diffraction peak based on the (113) plane appears at 2θ=43.3±0.5°. The diffraction peak based on the (104) plane appears at 2θ=35.1±0.5°. The diffraction peak due to the (116) plane appears at 2θ=57.5±0.5°, the diffraction peak due to the (018) plane appears at 2θ=61.3±0.5°, and the diffraction peak due to the (1010) plane appears at 2θ=76.9±0.5°.

[0042] The alumina powder of this embodiment preferably contains an alkali metal (AM) in an amount of 0.01% by mass or more and 0.5% by mass or less in terms of AM2O, and silicon (Si) in an amount of 0.01% by mass or more and 0.3% by mass or less in terms of SiO2. The content of the alkali metal (AM) is more preferably 0.01% by mass or more and 0.3% by mass or less in terms of AM2O. The content of silicon (Si) is more preferably 0.01% by mass or more and 0.2% by mass or less in terms of SiO2. The alkali metal (AM) is preferably one or both of sodium (Na) and potassium (K). By including these components, it is possible to further enhance the brilliance of the alumina powder. Particularly preferably, sodium (Na) is included in an amount of 0.01% by mass or more and 0.5% by mass or less in terms of Na2O. This makes it possible to more effectively suppress the glittering feeling of the alumina powder.

[0043] The alumina powder of the present embodiment preferably contains at least aluminum (Al), an alkali metal (AM), silicon (Si), and oxygen (O). However, other components (elements other than Al, AM, Si, and O) may be contained as long as the above-mentioned requirements are satisfied. Furthermore, the presence of impurities that are inevitably mixed in during the manufacturing process is permitted. One such other component is fluorine (F). Fluorine (F) is a component derived from an additive added during the manufacture of the alumina powder. That is, as described later, the additive added during the manufacture of the alumina powder contains fluorine (F). Most of the fluorine volatilizes during the firing process, but some may remain. The amount of fluorine in the alumina powder is typically 0.5% by mass or less, 0.3% by mass or less, or 0.1% by mass or less.

[0044] If other components (elements other than Al, AM, Si, and O) are contained in large amounts, the brilliance of the alumina powder may be impaired. Therefore, the content of other components is preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 1% by mass or less, particularly preferably 0.5% by mass or less, and most preferably 0.1% by mass or less. In particular, since iron (Fe) has the effect of coloring the alumina powder, it is preferable to suppress its content. Preferably, the content of iron (Fe) is 0.05% by mass or less in terms of iron oxide (Fe2O3).

[0045] The specific surface area (S BET ) is 0.1m 2 / g or more 5.0m 2 / g or less is preferable, and 0.3m 2 / g or more 2.0m 2 / g or less is more preferable. If the specific surface area is too large, the particle size of the alumina powder becomes small, which may reduce the sense of brilliance. On the other hand, it is difficult to produce an alumina powder with a small specific surface area.

[0046] The alumina powder of this embodiment has high chemical stability because it is mainly composed of α-alumina. In addition, it has a large average particle size and excellent dispersibility. Alumina powders with such characteristics are suitable for use in the fields of paints and cosmetics. However, the alumina powder of this embodiment is not limited to those used in paints and cosmetics. It can be used in known applications such as reinforcing materials and gas barrier materials mixed into plastics and resin films, structural members, tools, abrasives, fillers, spark plugs, insulators, electronic substrates, and refractories.

[0047] <<2. Manufacturing method of plate-like alumina powder>> The manufacturing method of the plate-like alumina powder of this embodiment is not limited as long as it satisfies the above-mentioned requirements. However, it is preferably manufactured by the following procedure. A preferred manufacturing method includes a step of preparing a raw material mixture containing aluminum hydroxide powder and an additive (raw material mixing step), and a step of holding and firing the raw material mixture at a temperature in the range of 1000°C to 1300°C for less than 20 hours (firing step). The raw material mixture contains an alkali metal (AM) in an amount of 0.01% by mass to 0.5% by mass calculated as AM2O, silicon (Si) in an amount of 0.1% by mass to 0.3% by mass calculated as SiO2, and fluorine (F) in an amount of 0.1% by mass to 5.0% by mass calculated as F. The heating rate in the step of firing the raw material mixture is 50°C / hour to 150°C / hour. If necessary, a post-treatment step may be provided after the firing step.

[0048] The manufacturing method of this embodiment is particularly characterized in that aluminum hydroxide powder is used as a raw material and the composition of the raw material mixture and the firing conditions are controlled within specific ranges, and this characteristic makes it possible to obtain alumina powder having a desired size and polycrystalline state, and as a result, maintaining a high sense of brilliance while suppressing dotted sparkle (glare). Each step will be described in detail below.

[0049] <Raw material mixing process> In the raw material mixing step, a raw material mixture containing aluminum hydroxide powder and additives is prepared. Aluminum hydroxide is a compound represented by the chemical formula Al(OH)3, and is dehydrated by heating to change into α-type aluminum oxide (α-alumina). Two types of aluminum hydroxide are known: gibbsite (γ-type aluminum hydroxide) and bayerite (α-type aluminum hydroxide). In this embodiment, either gibbsite or bayerite may be used. However, powder made of thermodynamically stable gibbsite is preferred.

[0050] As long as the alumina powder of the present embodiment can be obtained, the size of the aluminum hydroxide powder as the raw material is not particularly limited. However, the volume average particle size (D50) is preferably 0.5 μm or more and 15 μm or less. Alternatively, the specific surface area (S BET ) is 0.5m 2 / g or more 20m 2 / g or less. D50 is the cumulative 50% diameter in the particle size distribution on a volume basis determined by a laser diffraction / scattering particle size distribution analyzer. BET is a value obtained by measurement using N2 gas adsorption method.

[0051] The additive is a component that becomes liquid in the subsequent firing step and acts as a mineralizer. The additive contains at least silicon (Si) and fluorine (F), and may further contain an alkali metal (AM) as necessary. As described later, when the composition of the liquid phase component is appropriately controlled, the crystallization and grain growth of the alumina particles proceeds appropriately, and as a result, it is possible to obtain an alumina powder having a desired size and polycrystalline state.

[0052] Therefore, in order to obtain a desired alumina powder, it is important to appropriately control the composition of the raw material mixture containing additives. Specifically, the composition of the additives is adjusted so that the raw material mixture contains alkali metal (AM) in an amount of 0.01 mass% or more and 0.5 mass% or less in terms of AM2O, silicon (Si) in an amount of 0.1 mass% or more and 0.3 mass% or less in terms of SiO2, and fluorine (F) in an amount of 0.1 mass% or more and 5.0 mass% or less in terms of F. When the composition of the raw material mixture is within the above-mentioned range, it is possible to obtain an alumina powder having a desired size and polycrystalline state, and thus maintaining a high sense of brilliance while suppressing glittering. On the other hand, if the raw material mixture composition is inappropriate, it may have an adverse effect on the particle size and crystal state.

[0053] The amount of alkali metal (AM) in the raw material mixture is more preferably 0.01% by mass or more and 0.5% by mass or less in terms of AM2O. The alkali metal is preferably one or both of sodium (Na) and potassium (K), and particularly preferably sodium (Na). The amount of silicon (Si) in the raw material mixture is more preferably 0.10% by mass or more and 0.20% by mass or less in terms of SiO2. The amount of fluorine (F) in the raw material mixture is more preferably 0.1% by mass or more and 1.0% by mass or less in terms of F. By limiting the composition of the raw material mixture to within the above-mentioned range, the polycrystalline state of the alumina powder can be controlled within a more preferable range.

[0054] The additive contains at least silicon (Si) and fluorine (F). The additive may or may not contain an alkali metal (AM). The raw aluminum hydroxide powder may contain an alkali metal (AM) as an impurity. When the amount of alkali metal in the aluminum hydroxide powder is sufficient, the additive may not contain an alkali metal. On the other hand, when the amount of alkali metal in the aluminum hydroxide powder is insufficient, it is preferable to add an alkali metal as an additive. Furthermore, the additive may contain aluminum (Al). When the additive contains aluminum, this aluminum is incorporated into the alumina powder during the firing process.

[0055] As long as an alumina powder having a desired size and polycrystalline state is obtained, the additive may contain other components other than alkali metals (AM), silicon (Si), fluorine (F), aluminum (Al) and oxygen (O). However, if the amount of other components is excessively large, it may adversely affect the particle size and polycrystalline state. The content of other components is preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, and particularly preferably 1% by mass or less. The additive may not contain other components other than alkali metals (AM), silicon (Si), fluorine (F), aluminum (Al) and oxygen (O) in amounts exceeding the impurity amount.

[0056] According to a preferred embodiment, the additive contains aluminum fluoride (AlF3) and silicon oxide (SiO2). When the amount of alkali metal in the aluminum hydroxide powder is insufficient, it is preferred that the additive further contains one or both of an oxide (AM2O) and a carbonate (AM2CO3) of an alkali metal (AM). According to another preferred embodiment, the additive contains an alkali silicon fluoride (AM2SiF6). By using an appropriate amount of these compounds (AlF3, SiO2, AM2O, AM2CO3, AM2SiF6) as additives, it is possible to reliably produce an alumina powder having a desired size and polycrystalline state. In addition, these compounds are inexpensive and easily available. Therefore, a plate-like alumina powder can be obtained at a lower cost.

[0057] The raw material mixture may be prepared by mixing aluminum hydroxide powder and additives. The mixing may be performed by a known method. It may be performed in a dry manner or a wet manner. Dry mixing may be performed using a dry mixer such as an air blender, a V-type blender, a rocking blender, a Henschel mixer, or a Nauta mixer. In the case of wet mixing, a solvent such as water is added to the aluminum hydroxide powder and additives to form a slurry, and the obtained slurry may be mixed using a wet mixer such as a ball mill, an attritor, or a bead mill.

[0058] <Firing process> In the firing process, the resulting raw material mixture is fired at a temperature between 1000°C and 1300°C for less than 20 hours. This results in a fired product. During firing, aluminum hydroxide (Al(OH)3) is dehydrated and transformed into alpha-alumina (Al2O3). The alkali metals (AM), silicon (Si) and fluorine (F) in the raw material mixture become liquid oxides and act as mineralizers to promote the crystallization of alpha-alumina. In other words, the crystal structure changes during the transition from Al(OH)3 to alpha-alumina. The addition of mineralizers promotes the crystallization of alpha-alumina (corundum), making it possible to lower the transition temperature.

[0059] The mineralizer components (AM, Si, F) that become liquid during firing cover the surface of the alumina particles, and some of them penetrate into the inside of the particles. This liquid phase component has the function of promoting the diffusion and growth of particles. That is, some of the aluminum atoms (Al) from the surface of the alumina particles dissolve into the liquid phase, and the dissolved aluminum precipitates in another place on the particle surface. This causes the growth of the alumina particles. At this time, depending on the composition of the liquid phase component, a difference occurs in the growth direction of the alumina particles, and the growth rate changes. Therefore, if the composition of the liquid phase component is appropriately adjusted, the growth of the aluminum particle plate surface is controlled, and as a result, particles with high plate-likeness and a desired polycrystalline state are obtained. The liquid phase component also has the effect of smoothing the plate surface of the alumina particles. If the alumina particle surface has unevenness, the unevenness will preferentially diffuse into the liquid phase, and the unevenness will disappear. Therefore, if the composition of the liquid phase component is appropriately controlled, it is possible to obtain alumina powder with a desired size and polycrystalline state as well as a smooth surface.

[0060] If the firing temperature is less than 1000°C, the transition to α-alumina and grain growth may be insufficient. Therefore, it may be difficult to obtain alumina powder with excellent dispersibility. On the other hand, if the firing temperature is more than 1300°C, the particles may sinter together to form a strong sintered mass. In addition, the energy consumption for firing may be excessive, which may lead to an increase in manufacturing costs. The firing temperature is preferably 1000°C or more and 1200°C or less, and more preferably 1100°C or more and 1200°C or less. In addition, the firing time is preferably 10 hours or more and less than 20 hours. This can reliably ensure the transition to α-alumina and grain growth while preventing excessive sintering of the particles. The firing furnace is not limited as long as the desired alumina powder is obtained. However, from the viewpoint of effectively exerting the action of the additive during firing, a stationary furnace capable of firing using a closed firing container is preferable.

[0061] In the manufacturing method of this embodiment, the heating rate in the firing step is set to 50° C. / hour or more and 150° C. / hour or less. In controlling the polycrystalline state of the alumina powder, the heating rate during firing is important as well as the composition of the liquid phase components and the firing temperature. The larger (faster) the heating rate is, the larger the grain boundary length is. Therefore, the ratio (L2 / L1) of the total length (L2) of the grain boundaries to the perimeter (L1) of the alumina powder is larger. In contrast, the smaller (slower) the heating rate is, the smaller the ratio (L2 / L1) is. By adjusting the composition of the liquid phase components and the firing temperature within a predetermined range and adjusting the heating rate within a predetermined range, the ratio (L2 / L1) is controlled within a desired range, and as a result, it is possible to obtain an alumina powder with reduced scattered sparkle (glare). The heating rate described above is a heating rate at least in a temperature range of 25° C. (room temperature) to 1000° C.

[0062] <Post-processing> If necessary, the fired product obtained through the firing process may be subjected to post-treatment such as soda removal, crushing, and / or classification. In the soda removal treatment, excess alkali metal components attached to the fired product surface are removed. This allows the amount of alkali metal in the finally obtained alumina powder to be adjusted. The alkali metal components on the particle surface can be removed, for example, by washing and filtering the fired product. In the crushing treatment, mild mechanical energy is applied to the fired product to break the bonds of the aggregated particles formed during firing. The crushing treatment can be performed in a dry or wet manner using a crusher such as a pot mill, a pin mill, and / or a jaw crusher. In the classification treatment, particles are selected according to size to obtain alumina powder of the desired particle size. The classification treatment can be performed by a technique such as sieving, air classification, elutriation, and / or centrifugation. The post-treatment may be performed as necessary. If the desired alumina powder can be obtained after firing, the post-treatment may be omitted.

[0063] In this manner, the plate-like alumina powder of the present embodiment can be produced. The obtained alumina powder has a desired size and polycrystalline state, and has a smooth surface. Therefore, while maintaining a high sense of brilliance, the scattered shine (glare) is suppressed. Such alumina powder can be suitably used for various applications, including paints and cosmetics.

[0064] <<3. Paints and cosmetics>> The paint or cosmetic of this embodiment contains the above-mentioned plate-like alumina powder. The paint or cosmetic may contain the alumina powder alone or in a surface-treated form. The surface treatment may be performed by providing a surface treatment agent such as a silicon-based compound, an alkylsilane-based compound, and / or a fluorine-based compound on the particle surface of the plate-like alumina powder. The paint or cosmetic may contain a solvent or a resin in addition to the plate-like alumina powder. The solvent may be aqueous or non-aqueous. The paint or cosmetic may further contain known additives such as oils, pigments other than the plate-like alumina powder, fillers, surfactants, viscosity adjusters, preservatives, fragrances, moisturizers, bioactive ingredients, salts, chelating agents, neutralizing agents, and / or pH adjusters. EXAMPLES

[0065] The present invention will be described in more detail with reference to the following examples and comparative examples. However, the present invention is not limited to the following examples.

[0066] (1) Preparation of plate-shaped alumina powder [Examples 1 to 5 and Comparative Example 1] An aluminum hydroxide (gibbsite) powder (Nippon Light Metal Co., Ltd.) was prepared as the alumina source for Examples 1 to 3 and Comparative Example 1. Another aluminum hydroxide (gibbsite) powder (Nippon Light Metal Co., Ltd.) was prepared as the alumina source for Examples 4 and 5. The properties of the prepared aluminum hydroxide powder are shown in Table 1 below. Note that Na2O shown in Table 1 is the total value of the eluted sodium content on and near the crystal surface of the aluminum hydroxide and the uneluted sodium content incorporated in the crystal lattice, and f-Na2O is only the eluted sodium content on and near the crystal surface of the aluminum hydroxide.

[0067] Separately, aluminum fluoride (DO-FLUORIDE CHEMICALS CO., LTD.; AlF3), silicon oxide (Marukama Kamado Toryo Co., Ltd., Yukijirushi Silica SP-3; SiO2), sodium carbonate (Kanto Chemical Co., Ltd.; Na2CO3), and sodium silicofluoride (Kanto Chemical Co., Ltd., sodium hexafluorosilicate; Na2SiF6) were prepared as additives.

[0068] Next, the prepared aluminum hydroxide powder and additives were mixed to prepare a raw material mixture. The amount of additives was adjusted so that the content ratio of each additive in the raw material mixture was the value shown in Table 1 below. Mixing was performed by putting the raw materials in a bag and shaking them (manual method; Examples 1, 2, 4, and 5) or by using a rocking mixer (mechanical method; Example 3 and Comparative Example 1).

[0069] <Firing process> The obtained raw material mixture was put into a firing container, and the firing container was closed with a dedicated lid. The firing container with the lid was placed in a firing furnace and fired in the air. The firing was performed using an electric furnace or a shuttle kiln. During firing, the temperature was raised to the firing temperature at a heating rate of 100°C / hour, and then the temperature was maintained for 10 hours (Examples 1 to 5) or 20 hours (Comparative Example 1), and then naturally cooled. The firing temperature was 1100°C (Examples 1 to 5) or 1050°C (Comparative Example 1). After the temperature inside the furnace had dropped to its lowest, the firing container was removed from the furnace, and the fired product (alumina) was collected.

[0070] <Post-processing> The obtained fired product was subjected to post-treatment. The crushing strength was adjusted so as not to destroy the plate shape, and wet crushing was performed, followed by filtration to obtain a crushed product (alumina). The crushed product obtained was then dried overnight at 105°C using a dryer. After the crushing treatment, coarse particles and fine particles were removed.

[0071] In this manner, the plate-like alumina powders were produced in Examples 1 to 5 and Comparative Example 1. The production conditions for the plate-like alumina powder are summarized in Table 1 below.

[0072] [Comparative Example 2] In Comparative Example 2, a commercially available tabular alumina powder (Kinsei Matec Co., Ltd., YFA10030) was obtained and its characteristics were evaluated.

[0073] [Table 1]

[0074] (2) Evaluation The plate-like alumina powders obtained in Examples 1 to 5 and Comparative Examples 1 and 2 were used as samples, and various properties were evaluated as follows.

[0075] <Particle size distribution> The particle size distribution of alumina powder was measured using a laser diffraction / scattering particle size distribution analyzer (manufactured by Nikkiso Co., Ltd., Microtrac MT3300). Specifically, the alumina powder was directly placed into the input port of the measuring device and dispersed for 1 minute using the dispersion function installed in the device, and then the particle size distribution was measured. The average particle size (Dp50) was determined as the particle size corresponding to an integrated particle size distribution rate of 50% by volume.

[0076] <SEM Observation> Alumina powder was evaluated using a scanning electron microscope (manufactured by JEOL Ltd., JSM-F100; SEM) and image analysis software (ImageJ). Specifically, an SEM image of the obtained alumina powder was taken, and the particle size and thickness were measured by evaluating the particles (plate-like α-alumina particles) reproduced in the image using ImageJ, and the average particle size and average thickness were calculated. The average particle size was the average value of 80 particles, and the average thickness was the average value of 30 particles. Then, the ratio of the average particle size to the average thickness (average particle size / average thickness) was determined as the average aspect ratio.

[0077] In addition, analysis was performed by the electron backscatter diffraction (EBSD) method to examine the crystal state of the particles (plate-like α-alumina particles) constituting the alumina powder. Specifically, EBSD measurement was performed using a device in which a crystal orientation measuring device for an electron microscope and an analysis tool (TSL Solutions Co., Ltd., OIM EBSD system) were incorporated into a scanning electron microscope (manufactured by JEOL Ltd., JSM-6490A; SEM), and the crystal form of alumina was observed. At that time, the particle surface was observed, and the perimeter length (L1) of the particle on the particle surface, the total length (L2) of the grain boundaries on the particle surface, and the major axis (L3) of the particle were measured, and L2 / L1 and L2 / L3 were calculated. The same operation was performed on 30 particles, and the average value of L2 / L1 and the average value of L2 / L3 were determined.

[0078] <Crystal Phase> The crystal phase of the alumina powder was examined using an X-ray diffractometer (Rigaku Corporation, RINT UltimaIII). Specifically, the obtained alumina powder (sample) was placed on a glass sample plate, pressed so that the sample surface was flat to allow for selective orientation, and then measured with an XRD measurement device. CuKα was used as the X-ray source. It was then examined whether or not a diffraction peak based on α-alumina (corundum phase) was detected in the obtained X-ray diffraction pattern.

[0079] For the samples in which diffraction peaks due to α-alumina were detected, the intensities (heights) of the diffraction peaks due to the (006), (113), (104), (116), (018), and (1010) planes of α-alumina were calculated as I A , I B ,I C ,I D , I E and I F The peak intensity ratio I A / I B , I C / I B , I D / I B , I E / I B and I F / I B was calculated.

[0080] <Component analysis> The component analysis was performed using a scanning X-ray fluorescence analyzer (Rigaku Corporation, ZSX PrimusIV). Specifically, alumina powder was placed in a platinum crucible and set in a high-frequency melting device. After that, the crucible was preheated at 700°C for 60 seconds, and then rocked at 1200°C for 120 seconds to produce a glass bead sample. The glass bead sample was then evaluated using the scanning X-ray analyzer. The obtained data was compared with the data of the standard sample for the calibration curve to obtain the evaluation results.

[0081] <Specific surface area> Specific surface area (S BET) was evaluated by N2 gas adsorption method using a manual specific surface area measuring device (Micromeritics Instrument Corp., FlowSorbIII 2305 type).

[0082] <Glittering effect (dots of sparkle)> The glittering sensation of the plate-like alumina powder was evaluated. Specifically, five healthy adults (three men and two women) were selected as evaluators, who applied an appropriate amount (about 1 g) of the plate-like alumina powder to the back of their hands and visually observed the powder after application. They then gave a score according to the following evaluation criteria.

[0083] 3 points: The scattered shine (glare) is suppressed. 2 points: The sparkle is somewhat scattered 1 point: Strong sense of scattered sparkle

[0084] Then, for each sample, the scores of the five evaluators were averaged, and the obtained average value (rounded off to two decimal places) was used to evaluate the sense of dots (sense of glitter).

[0085] (3) Evaluation results The evaluation results obtained for Examples 1 to 5 and Comparative Examples 1 and 2 are summarized in Table 2 below.

[0086] In Examples 1 to 6, both the average particle size and the average thickness were within the ranges specified in this embodiment (average particle size 2 to 100 μm, average thickness 0.2 to 3.0 μm). In addition, the particles constituting the powder were polycrystalline, and the average value of the ratio (L2 / L1) of the total length of the grain boundaries (L2) to the circumferential length of the particle (L1) was within the range (0.30 to 2.0) specified in this embodiment. In addition, in Examples 1 to 3, the evaluation results of the scattered feeling were relatively high at 2.4 to 3.0.

[0087] In contrast, in Comparative Example 1, the average value of the ratio (L2 / L1) was small and did not meet the range (0.30 to 2.0) specified in this embodiment. Therefore, the evaluation result of the scattered feeling was low at 1.2. In addition, Comparative Example 2 was composed of single crystal particles.

[0088] [Table 2]

[0089] From the above results, it can be seen that the present embodiment provides a plate-like alumina powder and a manufacturing method thereof that have reduced scattered sparkle (glare) compared to conventional plate-like alumina powders, even though the particle size is the same.

Claims

1. A plate-like alumina powder which is composed of a plurality of plate-like α-alumina particles, has an average particle size of 2 μm or more and 100 μm or less as measured by SEM observation, and has an average thickness of 0.2 μm or more and 3.0 μm or less as measured by SEM observation, The plate-like α-alumina particles are polycrystalline, The plate-like alumina powder has an average ratio (L2 / L1) of the total length (L2) of the grain boundaries to the circumferential length (L1) of the plate-like alpha-alumina particles on the plate surfaces of the plate-like alpha-alumina particles of 0.30 or more and 2.00 or less.

2. The plate-like alumina powder according to claim 1 , wherein the average value of L2 / L1 is 0.50 or more and 1.50 or less.

3. 3. The plate-like alumina powder according to claim 1, wherein the average particle size is from 5 μm to 50 μm and the average thickness is from 0.3 μm to 1.0 μm.

4. A method for producing the plate-like alumina powder according to claim 1 or 2, preparing a raw material mixture containing aluminum hydroxide powder and an additive; and A step of firing the raw material mixture at a temperature in the range of 1000° C. to 1300° C. for less than 20 hours, The raw material mixture is an alkali metal (AM) 2 O equivalent of 0.01 mass % or more and 0.5 mass % or less, silicon (Si) is SiO 2 and fluorine (F) in an amount of 0.1% by mass to 5.0% by mass in terms of F, The method, wherein the heating rate in the step of calcining the raw material mixture is 50° C. / hour or more and 150° C. / hour or less.

5. The additive is an alkali silicofluoride (AM 2 SiF 6 ), or aluminum fluoride (AlF 3 ) and silicon oxide (SiO 2 5. The method of claim 4, comprising:

6. The additive is an oxide of an alkali metal (AM). 2 O) and carbonate (AM 2 CO 3 6. The method of claim 5, further comprising one or both of:

7. 5. The method of claim 4, wherein the alkali metal (AM) is one or both of sodium (Na) and potassium (K).

8. A paint or cosmetic comprising the platelet alumina powder according to claim 1 or 2.

Citation Information

Patent Citations

  • Brilliant pigment-containing coating composition and formation of composite coating film

    JP1998298458A

  • Hexagonal-plate-like boehmite, hexagonal-plate-like alumina, and method for producing them

    JP2003002642A

  • Pearlescent pigment with a large aspect ratio and method for manufacturing the same

    JP2010502774A

  • Method for manufacturing tabular boehmite-based and tabular alumina-based powder, tabular powder, and cosmetic containing the same

    JP2012071996A

  • α-ALUMINA FLAKE

    JP2014218424A